GOOGLE TRANSLATE SEBAGAI ALTERNATIF MEDIA PENERJEMAHAN TEKS BAHASA ASING KE DALAM BAHASA INDONESIA - Adi Alam (Universitas Muhammadiyah Jakarta, 2020)
The development of Information and Communication Technology (ICT) is progressing very rapidly. Due to the strong era of globalization where computers and the dynamic internet become facilities that have dominated various life activities, so educational activities also require the availability of these facilities. Google Translate becomes one of the translation machines that can be used by academics in translating literature written in foreign languages. Google Translate is one of the media that can make it easier for someone to translate text from various languages into the desired language. This paper uses a descriptive qualitative approach with this literature study method aimed at describing the process of translating foreign language texts and pronunciation into appropriate Indonesian. The media can be used to translate text, both by word, phrase, clause, sentence, and even discourse. However, it is often found errors and irregularities in the translation of the entered text. The results of this study are that academics are greatly helped by the existence of the Google Translate application as a learning medium. Despite the lack of this application, learning academics still have a positive perception of their use. They believe that the results of the translation will remain accurate as long as they can match the context.